Loss Due to Data Leaks: How is the Legal Protection for Account Owners on Marketplace? (Universitas Negeri Semarang, 2020)
In the digital age, there are a lot of people or society who choose e-commerce rather than the conventional transaction. E-commerce usually done in online marketplace applications such as Tokopedia, Bukalapak, Traveloka, and so on. Based on the data, Indonesia ranks as one of the highest e-commerce growth rate in the world. This is a good sign, because it means that marketplace companies in Indonesia can also compete and have a great opportunity to be more global. However, as a result of these developments, of course there are also negative impacts that come together. One of the negative impacts is the issue of security/security of the linked accounts in the marketplace application. A lot of data-leak phenomena occur frequently and this is an urgent matter to be prevented and resolved. Marketplace’s account owners must have a legal things that protect them and prevent any various kinds of losses that can arise due to data leakage. And the marketplace platform providers also have to make some policies to protect their app users from the data leakage.